The impact of firm specific news on implied volatilities - Donders, Monique W.M.; Vorst, Ton C.F. (Journal of Banking & Finance, 1996)
We study the implied volatility behavior of call options around scheduled news announcement days. Implied volatilities increase significantly during the pre-event period and reach a maximum on the eve of the news announcement. After the news release, implied volatility drops sharply and gradually moves back to its long-run level. Only on the event date are movements in the price of the underlying significantly larger than expected. These results confirm the theoretical results of Merton (1973).